1968
DOI: 10.1071/bi9681215
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Selection for A Quantitative Character in Drosophila. I.Single-Sex Selection

Abstract: SummarySelection for abdominal bristle number was done in six lines, three with selection in females only and three in males only_ Selection was equally effective (for a given selection differential) when carried out in either sex, even though more than one-third of the additive genetic variation was sex linked_ Most response in a given sex was found in the treatment selected in that sex. Relaxed lines failed to show fluctuating scores in the two sexes as predicted by Griffing (1965). Epistatic decay may have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

1972
1972
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 12 publications
4
34
0
Order By: Relevance
“…In this same experiment, there was significant opposing selection on male and female bill colour that is consistent with zebra finch bill colour being displaced from sex-specific optima (Price, 1991). In other species, estimates of genetic correlations between the sexes have also been very high for morphological characters (Harrison, 1953;Frankham, 1968aFrankham, , 1968bCrowley & Atchley, 1986;Crowley et al, 1986;Rogers & Mukherjee, 1992). Therefore, genetic covariances between traits expressed in males and females may cause traits to be displaced from their sex-specific optima in other species for evolutionarily long time periods (Lande, 1 980a).…”
Section: Genetic Estimatessupporting
confidence: 50%
See 1 more Smart Citation
“…In this same experiment, there was significant opposing selection on male and female bill colour that is consistent with zebra finch bill colour being displaced from sex-specific optima (Price, 1991). In other species, estimates of genetic correlations between the sexes have also been very high for morphological characters (Harrison, 1953;Frankham, 1968aFrankham, , 1968bCrowley & Atchley, 1986;Crowley et al, 1986;Rogers & Mukherjee, 1992). Therefore, genetic covariances between traits expressed in males and females may cause traits to be displaced from their sex-specific optima in other species for evolutionarily long time periods (Lande, 1 980a).…”
Section: Genetic Estimatessupporting
confidence: 50%
“…Genetic covariances between the sexes have been reported for various morphological traits in mice (Eisen & Legates, 1966;Eisen & Hanrahan, 1972), friut flies (Harrison, 1953;Frankham, 1968aFrankham, , 1968bCrowley et at., 1986;Crowley & Atchley, 1988) and humans (Rogers & Mukherjee, 1992). The occurrence of relatively large genetic covariances between the sexes in these animals indicate that the selective pressures in one sex would have a large effect on the other sex and thus the evolution to sex-specific optima may proceed very slowly (Lande, 1980a;Lande & Arnold, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Selection for sexual dimorphism has been moderately successful for abdominal bristle number in Drosophila melanogaster (Harrison 1953;Frankham 1968b) and body weight in mice (Korkman 1957). Frankham (1968a) found that single-sex selection changed the sexual dimorphism for abdominal bristle number in D. melanogaster since selection response was consistently greater in the selected sex.…”
Section: Introductionmentioning
confidence: 99%
“…Frankham (1968aFrankham ( , 1968b defined the sex dimorphism ratio as male mean/female mean and stated that it should be free of scale effects. Although the ratio is only scale-free under certain restrictive assumptions, it is reported here for comparative purposes since Korkman (1957) o Replicate I (Mfl-mfl).…”
Section: (B) Observed Response In Sexual Dimorphismmentioning
confidence: 99%
See 1 more Smart Citation